The Future of Journalism Artificial Intelligence Facilitates Agenda-Setting for Bacaini.ID in the Kediri Mayoral Election - Danny Kunto Wibisono; Hari Tri Wasono; Irwa Rochimah Zarkasi (Universitas Multimedia Nusantara, 2025)
The presence of artificial intelligence (AI) machines brings a significant transformation for journalists in collecting extensive data information, extracting patterns, and facilitating content more quickly and efficiently, allowing journalists to focus on in-depth investigations. AI can also be used to create personalized content, which can assist media in agenda-setting and enhance literacy among the audience. This research illustrates this using the Mediated Data Model Of Communication Flow. The approach used is a mixed method, analyzing data sourced from big data applications and AI Intelligence Media Analytics (IMA), as well as Intelligence Social Analytics (ISA), with the topic